Alan S. Kahan, Aristocratie Liberalism: The Social and Political Thought of Jacob Burckhardt, John Stuart Mill and Alexis de Tocqueville - Λάβδας Κώστας (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2015)
[Δεν διατίθεται περίληψη / no abstract available]